Strategi Pengelolaan Event, Sponsorhip Dan Patnership Serta Konten Media Sosial Pada PT. Telkomsel Surabaya - Visi Ari Pratiwi; Yanda Bara Kusuma (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
PT Telekomunikasi Indonesia Tbk is a company that provides network services. PT Telkomsel Surabaya oversees several card products, namely Telkomsel Postpaid Card, Telkomsel Prepaid Card, and By.U Card. In addition, they also offer modem products such as Orbit and Indihome as part of their sales portfolio. Direct selling is one of the most frequently used promotional and marketing methods by Telkomsel, including organizing events and collaborating with various events through sponsorship and partnerships. This research is written using a descriptive method, analyzing the results directly from the company during the internship period.